2016
DOI: 10.1155/2016/5318176
|View full text |Cite
|
Sign up to set email alerts
|

In VitroGrowth Inhibitory Activities of Natural Products from Irciniid Sponges against Cancer Cells: A Comparative Study

Abstract: Marine sponges of the Irciniidae family contain both bioactive furanosesterterpene tetronic acids (FTAs) and prenylated hydroquinones (PHQs). Both classes of compounds are known for their anti-inflammatory, antioxidant, and antimicrobial properties and known to display growth inhibitory effects against various human tumor cell lines. However, the different experimental conditions of the reported in vitro bioassays, carried out on different cancer cell lines within separate studies, prevent realistic actual dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In fact, the IC50 analysis (Figure 1B) showed a value of 199.9 µg/mL (±3.12) for NHEM, whilst for melanoma cancer cells, it was between 20-80 µg/mL, suggesting that the antiproliferative effect of iSP was specific to cancer cells. Since MTT assay is an indirect analytical method to evaluate cell proliferation, we confirmed the antiproliferative effect of iSP by performing a carboxyfluorescein succinimidyl ester (CFSE) assay [16]. In particular, A375 cells were selected, given their lower IC50 value (26.08 ± 5.47) and their aggressive phenotype [25].…”
Section: Isp Treatment Affected the Proliferation Rate Of Human Melan...mentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, the IC50 analysis (Figure 1B) showed a value of 199.9 µg/mL (±3.12) for NHEM, whilst for melanoma cancer cells, it was between 20-80 µg/mL, suggesting that the antiproliferative effect of iSP was specific to cancer cells. Since MTT assay is an indirect analytical method to evaluate cell proliferation, we confirmed the antiproliferative effect of iSP by performing a carboxyfluorescein succinimidyl ester (CFSE) assay [16]. In particular, A375 cells were selected, given their lower IC50 value (26.08 ± 5.47) and their aggressive phenotype [25].…”
Section: Isp Treatment Affected the Proliferation Rate Of Human Melan...mentioning
confidence: 97%
“…These metabolites were detected by comparing their exact masses with those recorded in databases, e.g., the Dictionary of Natural Products (DNP) and SciFinder based on their fragmentation pattern in the MSMS spectra. Marine sponges belonging the genus Ircinia are known to be a very rich source of terpenoids, which have been found to possess diverse bioactivities [14][15][16]. Hahn et al 2014 [17] reported the isolation of PPARδ agonistic monocyclofarnesol-derived sesquiterpenoids and their hydroxylated analogues from Ircinia sp., including compound 1.…”
Section: Metabolic Profile Of I Ramosa Ethyl Acetate Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work [ 60 ], three prenylated-hydroquinones ( 15 , 16 , 17 ), in addition to three known furanosesterpene tetronic acids (iricinin 1 ( 19 ), sarcotin A ( 20 ), and variabilin ( 21 )) were purified from three Sarcotragus sponge species that were collected from Tunisian coasts: S. spinosulus from Tabarka and Monastir; S. fasciculatus , collected from Monastir; and S. foetidus collected from Cap Zebib. Comparing the inhibitory activity of the six compounds on viability of a panel of cancer cells with different sensitivity to pro-apoptotic stimuli, the polyprenyl-hydroquinones displayed greater potency than furanosesterpene tetronic acids, and only the hydroxylated polyprenyl-hydroquinone showed IC 50 < 10 M in all cell lines that were tested [ 60 ].…”
Section: Pharmacological Actions and Potential Therapeutic Applicationsmentioning
confidence: 99%